Chronic Low Back Pain with and without Concomitant Osteoarthritis: A Retrospective, Longitudinal Cohort Study of Patients in England - Greg Coates; Peter Clewes; Christoph Lohan; Hannah Stevenson; Robert Wood; Theo Tritton; Roger D. Knaggs; Alastair J. Dickson; David A. Walsh (International Journal of Clinical Practice)
Objective. Despite the high prevalence of chronic low back pain (CLBP) and osteoarthritis (OA), few estimates of the economic cost of these conditions in England have been published. The aim of the present analysis was to characterise the economic burden of moderate-to-severe pain associated with CLBP + OA and CLBP alone compared with general population-matched controls without CLBP or OA. The primary objective was to describe the total healthcare resource use (HCRU) and direct healthcare costs associated with the target patient populations. Secondary objectives were to describe treatment patterns and surgical procedures. Methods. This was a retrospective, observational cohort study of patients receiving healthcare indicative of moderate-to-severe chronic pain associated with CLBP, with or without OA. We used linked longitudinal data from the Clinical Practice Research Datalink GOLD and Hospital Episode Statistics (HES). Patients (cases) were matched 1 : 1 with controls on age, sex, comorbidity burden, GP practice, and HES data availability. Results. The CLBP-alone cohort comprised 13 554 cases with CLBP and 13 554 matched controls; the CLBP + OA cohort comprised 7803 cases with both OA and CLBP and 7803 matched controls. Across all follow-up periods, patients with CLBP alone and those with CLBP + OA had significantly more GP consultations, outpatient attendances, emergency department visits, and inpatient stays than controls (all p < 0.0001). By 36 months after indexing, the mean (SD) per-patient total direct healthcare cost in the CLBP-alone cohort was £5081 (£5905) for cases and £1809 (£4451) for controls (p < 0.0001); in the CLBP + OA cohort, the mean (SD) per-patient total direct healthcare cost was £8819 (£7143) for cases and £2428 (£4280) for controls (p < 0.0001). Conclusion Moderate-to-severe chronic pain associated with CLBP—with or without OA—has a substantial impact on patients and healthcare providers, leading to higher HCRU and costs versus controls among people with CLBP alone or together with OA.